Evaluation of epidural detomidine with and without lignocaine and its reversal by atipamezole in Sahiwal calves - Tiwari, S K; Mishra, U K; Mishra, O P (The Indian Journal of Animal Sciences, 2012)
Epidural administration of detomidine (@50µg/kg) with and without hgnocaine (0.22 mg/kg) in 20 healthy Sahiwal calves caused quick onset and longer duration of analgesia (138.00±4 26 versus 90.00±6.45 min) compared to detomidine alone. The transient bradycardia, respiratory depression. ruminal stasis were compensated within 2 hr after administration of drugs. There were nonsignificant changes in haematological profiles. Serum glucose was significanlly (P<0.05) increased and it persisted up to 2 hr in all the animals. Administration of atipamezole (@ 50µg/kg IV) caused early arousal from sleep (1.25± 0.12 min) and animals were able to walk by 4.00 ±0.14 min. Atipamezole also reversed the bradycardia, respiratory depression and ruminal stasis induced by epidural detomidine alone or with lignocaine. Thus epidural detomidine with and without lignocaine can safely be used for undertaking surgical manoeuvres of abdomino-pelvic region in Sahiwal cows.